KEANEKARAGAMAN JENIS Nepenthes (KANTONG SEMAR) DATARAN RENDAH DI KALIMANTAN TENGAH - Mansur, Muhammad (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Diversity on the lowland pitcher plants (Nepenthes spp.) in Central Kalimantan were conducted between August 2005 and September 2006 at three locations study. That is: Barito Ulu, Sebangau and Kasongan district. Survey inventories were used to determine the diversity of Nepenthes at the study site. We found sixteen Nepenthes at study area, divided nine Nepenthes species; N. albomarginata, N. ampullaria, N. gracilis, N. hirsuta, N. mirabilis, N. rafflesiana, N. reinwardtiana, N. stenophylla, one unidentified Nepenthes species and seven natural hybrid; N. xhookeriana (N. rafflesiana x N. ampullaria), N. xtrichocarpa (N. gracilis x N. ampullaria), N. xneglecta (N. gracilis x N. mirabilis), N. mirabilis x ampullaria, N. mirabilis x rafflesiana, N. reinwardtiana x N. mirabilis and N. reinwardtiana x gracilis. Heath forest and peat swamp forest are generaly the habitat of lowland Nepenthes at Central Kalimantan.